Reduced Levels of Tissue Inhibitors of Metalloproteinases in UVB‐Irradiated Corneal Epithelium. (25th August 2016) - Ardan, Taras; Němcová, Lucie; Bohuslavová, Božena; Klezlová, Adéla; Popelka, Štěpán; Studenovská, Hana; Hrnčiarová, Eva; Čejková, Jitka; Motlík, Jan
Abstract: Tissue inhibitors of metalloproteinases (TIMPs) are the major endogenous regulators of metalloproteinase activity in tissues. TIMPs are able to inhibit activity of all known matrix metalloproteinases (MMPs) and thus participate in controlling extracellular matrix synthesis and degradation. We showed previously elevated expressions of MMPs in the rabbit corneal epithelium upon UVB exposure and suggested that these enzymes might be involved in corneal destruction caused by excessive proteolysis. The aim of this study was to investigate TIMPs in the corneal epithelium after UV irradiation using immunohistochemical and biochemical methods. We found that as compared to control rabbit corneas where relatively high levels of TIMPs were present in the epithelium, repeated irradiation of the cornea with UVB rays (not with UVA rays of similar doses) significantly decreased TIMPs in corneal epithelial cells. The results of this study point to the suggestion that the decrease in TIMPs in the corneal epithelium after UVB irradiation contributes to increased proteolytic activity of MMPs in UVB‐irradiated corneal epithelium found previously. Abstract : We describe the effects of repeated irradiation of rabbit cornea with UV rays on the expression of tissue inhibitors of metalloproteinases (TIMPs), employing an in vivo model of damaged rabbit cornea and immunohistochemical and biochemical techniques. We demonstrate a significant decrease in the expression of these proteins upon UVB (but not UVA) irradiation. Our results point to the suggestion that insufficient inhibition of metalloproteinases due to decreased expression of TIMPs in corneas irradiated by UVB rays may contribute to excessive proteolysis of corneal proteins and corneal damage by matrix metalloproteinases (MMPs) investigated previously.